2001
DOI: 10.1021/jo010590z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Vicarious Nucleophilic Substitution of Hydrogen Mechanism via Studies of Competition between Substitution of Hydrogen, Deuterium, and Fluorine

Abstract: Relations of rates of the vicarious nucleophilic substitution of hydrogen (VNS) and S(N)Ar substitution of fluorine in 2-fluoronitrobenzenes with chloroalkyl aryl sulfone carbanions were determined from competitive experiments carried out at various concentrations of base. The observed dependence of the VNS/S(N)Ar rate ratio on the base concentration confirmed the two-step mechanism of the VNS, which consists of reversible formation of sigma(H) adducts of the alpha-chlorocarbanion to nitroarene, followed by ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 24 publications
4
35
0
4
Order By: Relevance
“…After final protonation, the substituted nitroarene or -heteroarene is obtained (Scheme 1). [7][8][9][10] It has been reported that the solvent, the nature and concentration of the base, and the steric demand of the carbanion have a considerable influence on the ratio of isomeric products. [11] When there is a high excess of the base, H À X elimination is faster than the retroaddition of the s H -adduct, and the formation of the s H -adducts becomes irreversible.…”
Section: Introductionmentioning
confidence: 99%
“…After final protonation, the substituted nitroarene or -heteroarene is obtained (Scheme 1). [7][8][9][10] It has been reported that the solvent, the nature and concentration of the base, and the steric demand of the carbanion have a considerable influence on the ratio of isomeric products. [11] When there is a high excess of the base, H À X elimination is faster than the retroaddition of the s H -adduct, and the formation of the s H -adducts becomes irreversible.…”
Section: Introductionmentioning
confidence: 99%
“…These findings prompted us to examine the process by ESR spectroscopy. Despite numerous previous attempts to study the mechanism of vicarious nucleophilic substitution of hydrogen [35][36][37], the problem concerning elementary steps of this process remains unclear. There is a concept according to which the reaction follows a polar mechanism involving intermediate formation of σ H complex [1,4,6,8,11,12].…”
Section: Ii-ivmentioning
confidence: 99%
“…[18] Much less attention has been paid to the question of how the σ H adducts are formed. Formation of the anionic σ adducts of carbanions to nitroarenes is a common initial step for the VNS reaction, the S N Ar reaction of halogens or other leaving groups in nitroaromatic rings and some other processes.…”
Section: Introductionmentioning
confidence: 99%